The Influence of Burnout and Teamwork on Organizational Commitment in Pekanbaru City Branch Family Pharmacy Employees - Abael, Fadlan Rafif; Hendriani, Susi; Nasution, Hafiza Oktasia (CV. Rayyan Dwi Bharata, 2024)
This study aims to look at the effect of Burnout and Teamwork on Organizational Commitment in Employees of the Family Pharmacy, Pekanbaru City Branch. This type of research is using quantitative research. The population in this study were all employees of the technician section totaling 102 people. This study used employees of the technician section of the Pekanbaru City Branch of the Family Pharmacy as the object of research. The sampling method uses saturated samples, namely 102 respondents. The analysis method used in processing this research data is descriptive statistical analysis, classical assumption test, multiple linear regression analysis and the coefficient of determination using a significance level of 0.05. The data processing of this research uses the help of SPSS 23 software. The results showed that there was a negative and significant influence between burnout on organizational commitment. There is a positive and significant influence between teamwork on organizational commitment. There is a simultaneous positive and significant influence between burnout and teamwork on organizational commitment.